Early activation and recruitment of invariant natural killer T cells during liver ischemia-reperfusion: the major role of the alarmin interleukin-33 - Robin, Aurélie; Mackowiak, Claire; Bost, Romain; Dujardin, Fanny; Barbarin, Alice; Thierry, Antoine; Hauet, Thierry; Pellerin, Luc; Gombert, Jean-Marc; Salamé, Ephrem; Herbelin, André; Barbier, Louise (Frontiers in Immunology, 2023)
Over the past thirty years, the complexity of the αβ-T cell compartment has been enriched by the identification of innate-like T cells (ITCs), which are composed mainly of iNKT cells and MAIT cells. Based on animal studies using ischemia-reperfusion (IR) models, a key role has been attributed to iNKT cells in close connection with the alarmin/cytokine interleukin (IL)-33, as early sensors of cell-stress in the initiation of acute sterile inflammation (ASI). Here we have investigated whether the new concept of a biological axis of circulating iNKT cells and IL-33 applies to humans, and may be extended to other ITC subsets, namely MAIT and γδ-T cells, in the ASI sequence occurring during liver transplant (LT). From a prospective biological collection of recipients, we reported that LT was accompanied by an early and preferential activation of iNKT cells, as attested by almost 40% of cells having acquired CD69 expression at the end of LT (i.e. 1-3 hours after portal reperfusion), as opposed to only 3-4% of conventional T cells. Early activation of iNKT cells was positively correlated with the systemic release of the alarmin IL-33 at graft reperfusion. Moreover, in a mouse model of hepatic IR, iNKT cells were activated in the spleen, and recruited in the liver in WT mice, as early as the first hour after reperfusion, whereas this phenomenon was virtually missing in IL-33-deficient mice. Although to a lesser degree than iNKT cells, MAIT and γδ-T cells also seemed targeted during LT, as attested by 30% and 10% of them acquiring CD69 expression, respectively. Like iNKT cells, and in clear contrast to γδ-T cells, activation of MAIT cells during LT was closely associated with both release of IL-33 immediately after graft reperfusion and severity of liver dysfunction occurring during the first three post-operative days. All in all, this study identifies iNKT and MAIT cells in connection with IL-33 as new key cellular factors and mechanisms of ASI in humans. Further investigations are required to confirm the implication of MAIT and iNKT cells, and to precisely assess their functions, in the clinical course of sterile inflammation accompanying LT.